Grounding and improving assessment in higher education: a way of promoting quality education - Fialho, Isabel; Cid, Marília; Coppi, Marcelo (Frontiers in Education, 2023)
In this paper we describe an experience that took place in a Portuguese public institution of higher education, within the scope of a pedagogical training course “Grounding and Improving Pedagogical Assessment in Higher Education”, created with the purpose of providing tools for the improvement of the pedagogical process, particularly with regard to assessment. In addition to the theorization that justifies the importance of pedagogical training in order to improve the quality of higher education, we describe and evaluate the impact of the course based on a questionnaire to identify teachers’ conceptions of assessment, which was applied before and after training.